2017
DOI: 10.1186/s12906-017-1883-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial potential and quantification of aloin and aloe-emodin in Aloe vera collected from different climatic regions of India

Abstract: BackgroundIn this study, Aloe vera samples were collected from different climatic regions of India. Quantitative HPTLC (high performance thin layer chromatography) analysis of important anthraquinones aloin and aloe-emodin and antiplasmodial activity of crude aqueous extracts was done to estimate the effects of these constituents on antiplasmodial potential of the plant.MethodsHPTLC system equipped with a sample applicator Linomat V with CAMAG sample syringe, twin rough plate development chamber (20 x 10 cm), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 44 publications
(44 reference statements)
5
53
0
Order By: Relevance
“…The relative variation in parasite suppression activity among doses might be due to variation in the amount of secondary metabolites contents in the leaf latex of Aloe weloensis. This show that Aloe weloensis is endowed with a very good antimalarial activity and concordant to promising antimalarial activity of Aloe vera, Aloe pulcherrima and Aloe megalacantha in the genus Aloe (19)(20)(21). In another studies, signi cant dose-dependent parasite suppression was demonstrated after administration of Aloe macrocarpa, Aloe debrana and Aloe sinana which indicate a promising antimalarial activity and providing the scienti c evidence for the folkloric use of the plant (41,42).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The relative variation in parasite suppression activity among doses might be due to variation in the amount of secondary metabolites contents in the leaf latex of Aloe weloensis. This show that Aloe weloensis is endowed with a very good antimalarial activity and concordant to promising antimalarial activity of Aloe vera, Aloe pulcherrima and Aloe megalacantha in the genus Aloe (19)(20)(21). In another studies, signi cant dose-dependent parasite suppression was demonstrated after administration of Aloe macrocarpa, Aloe debrana and Aloe sinana which indicate a promising antimalarial activity and providing the scienti c evidence for the folkloric use of the plant (41,42).…”
Section: Discussionsupporting
confidence: 54%
“…The latex of Aloe weloensis leaf showed antibacterial effect against gram negative and gram positive strains (17). The leaf latex of the plant has been used in folk medicine against malarial and others human ailment in Ethiopia (18).The leaf latex and isolated compounds of Aloe vera, Aloe pulcherrima and Aloe megalacantha, a similar plant species, possessed signi cant antimalarial activity (19)(20)(21).As a result, Aloe weloensis may have similar effect as all plants belong to the same genus. Therefore, the current study was aimed to investigate antimalarial activity of the leaf latex of Aloe weloensis.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the studies included in this review are discussed and presented as Tables 1 and 2. [6][7][8] In one of the studies included for review, chloroquine (CQ)-sensitive strain 3D7 and CQ-resistant strain INDO of P. falciparum were cultured in vitro on O + ve human erythrocytes and the toxicity with HeLa cells tested. The extracts of experimental plants were evaluated for their antiplasmodial activity against the culture.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, aloe‐emodin showed good antiplasmodial activity in a dose‐dependent manner. The antiplasmodial EC 50 value of aloe‐emodin was 22 μg/ml (Kumar, Yadav, Yadav, Rohilla, & Yadav, ).…”
Section: Pharmacologymentioning
confidence: 99%